A qualitative study exploring the relationship between mothers' vaccine hesitancy and health beliefs with COVID-19 vaccination intention and prevention during the early pandemic months - Kimberly K. Walker; Katharine J. Head; Heather Owens; Gregory D. Zimet (Taylor & Francis Group, 2021)
Vaccine hesitancy is a top ten global health threat that can negatively impact COVID-19 vaccine uptake. It is assumed that vaccine refusers hold deep, negative beliefs, while acceptors hold strong, positive beliefs. However, vaccine hesitancy exists along a continuum and is multidimensional, varying by time, place, vaccine, subgroup, and person. Guided by the Health Belief Model and vaccine hesitancy frameworks, the study purpose was to qualitatively explore maternal COVID-19 threat perceptions and willingness to accept a COVID-19 vaccine in light of their expressed vaccine hesitancy toward past school required and routinely recommended vaccines and the HPV vaccine for their children. Researchers conducted twenty-five interviews with US Midwestern mothers during the early COVID-19 pandemic months. Mothers were grouped by vaccine hesitancy categories and thematic analysis was used to analyze the data within and across categories. Results showed that prior vaccine hesitancy attitudes and behavior did not fully capture maternal acceptance of COVID-19 vaccine or perception of COVID-19 threat. Perceptions of COVID-19 threat did influence mothers' decisions about COVID-19 protective behaviors (e.g., handwashing, mask wearing, and distancing). However, mothers were hesitant to accept the COVID-19 vaccine across vaccine hesitancy categories, primarily citing concerns about safety, efficacy, and confusion over conflicting information as barriers to immediate COVID-19 vaccine acceptance. Findings indicate that mothers cannot be grouped together based on hesitancy about, or acceptance of, other vaccines for purposes of assuming COVID-19 preventive behavior adherence or anticipated COVID-19 vaccine acceptance.